IMPLEMENTASI ALGORITMA C4.5 UNTUK ANALISIS DAMPAK NEGATIF GELOMBANG ELEKTROMAGNETIK TELEPON SELULER TERHADAP OTAK PADA PERIODE 2019-2023 - Muhammad Fadly Yassin; Beni Rahmat Jaya Nazara; Dilvan Qiblatain; Kemas Muhammad Rafli Azhary; Muhammad Rizky Andika; Farhan Aditya Hidayatulloh; Baginda Oloan Lubis (Jurnal Humaniora & Sosial Sains, 2025)
Electromagnetic waves are formed from a combination of interacting electric and magnetic waves. The source of these waves can come from natural phenomena or man-made devices. Electromagnetic waves can propagate in all directions (omnidirectional) or in a directional manner, depending on the device and media used. As technology advances, the intensity of electromagnetic radiation from various devices continues to increase, with varying impacts on human health. Excessive and prolonged use of mobile phones can increase the risk of health problems, such as brain tumors (glioma and acoustic neuroma), as well as impaired cognitive function, including working memory deficits and behavioral changes that indicate damage to the hippocampus. This shows that radiation from mobile phones has a real impact on brain health. For this reason, disseminating information on how to prevent the negative impacts of mobile phones is very important, especially for vulnerable groups such as children and adolescents. In order to further understand the impact of electromagnetic waves, a study was conducted using the C4.5 algorithm which produces a decision tree model. This analysis provides insight into risk patterns, where the duration of mobile phone use and the distance of the device from the head are the main factors that affect brain health. The results of the study showed that using a mobile phone for more than 4 hours per day, especially at close range (less than 10 cm), significantly increased the risk of health problems such as headaches, sleep disorders, and decreased cognitive function. These findings emphasize the importance of using mobile phones wisely to minimize health risks.